MENJADI ILMUWAN CILIK: MENINGKATKAN KEMAMPUAN MERUMUSKAN HIPOTESIS MELALUI EKSPERIMEN SEDERHANA TENTANG PERTUMBUHAN BIJI-BIJIAN - Badridduja; Muhamad Sofian Hadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aimed to measure the effectiveness of project-based learning (PBL) in improving the ability of third-grade elementary school students to formulate hypotheses. The subjects of this study were 24 third-grade students at SDI Tebuireng Abdul Wahid Hasyim. The research method used was a pre-experimental design with a one-group pretest-posttest design. Data was collected through observation sheets, student worksheets, and assessment rubrics. The results showed a significant increase in students' ability to formulate hypotheses after following project-based learning. This improvement was due to the active involvement of students in the learning process, the relevance of the material to everyday life, and teacher support. The implications of this study are the importance of integrating project-based learning into the curriculum to improve the quality of student learning.